CORRECTION OF INTESTINAL DISBACTERIOSIS IN CHILDREN WITH CHRONIC HEPATITIS B ASSOCIATED WITH LAMBLIASIS - Nargiza F. Nurmatova (Central Asian Journal of Medicine, 2023)
Analysis and evaluation of the state of intestinal microbiocenosis in 85 children with chronic hepatitis B associated with lambliasis for the purpose of correction of disbiotic disorders in the intestine of children with individual approaches to the treatment choice.